The Detection of Spatially Resolved Protostellar Outflows and Episodic Jets in the Outer Galaxy - Toki Ikeda; Takashi Shimonishi; Natsuko Izumi; Hiroyuki Kaneko; Satoko Takahashi; Kei E. I. Tanaka; Kenji Furuya; Chikako Yasui (The Astrophysical Journal, 2025)
We present the first detection of spatially resolved protostellar outflows and jets in the outer Galaxy. We observed five star-forming regions in the outer Galaxy (Sh 2-283 and NOMF05-16/19/23/63; galactocentric distance = 15.7–17.4 kpc) with the Atacama Large Millimeter/submillimeter Array. Toward Sh 2-283, we have detected distinct outflow (∼5–50 km s ^−1 ) and jet components (∼50–100 km s ^−1 ) associated with the protostar in CO(3–2) emission. The outflows and jets are well collimated, with the jets exhibiting multiple bullet structures. The position–velocity diagram along the CO flow axis shows two characteristic structures: (a) the flow velocity, which linearly increases with the position offset from the core center (the Hubble-like flow); and (b) the continuous velocity components of the periodical flows (spine-like structures), which may indicate episodic mass ejection events. The time intervals of the mass ejection events are estimated to be 900–4000 yr, based on the slopes of these spine-like structures. These characteristics align with those of nearby protostellar systems, indicating that early star formation in low-metallicity environments, such as the outer Galaxy, resembles that in the inner Galaxy. In contrast to the physical similarities, the N (SiO)/ N (CO) ratio in the jet bullet appears to be lower than that measured in the low-mass protostellar sources in the inner Galaxy. This may indicate a different shock chemistry or different dust composition in the outer Galaxy source, although non–local thermodynamic equilibrium effects could also affect the observed low N (SiO)/ N (CO) ratio. We also report the new detection of four other outflow sources in the outer Galaxy.